Psychiatric practice from a bioethical perspective (Review) (REDEL. Revista Granmense de Desarrollo Local, 2023)
The development of science in general and particularly those of health, is marked by biomedical technological recreation, which has endowed the specialist with the medicine of new knowledge that strengthens their creative abilities in care for the health-disease process. This requires the constant search from science and the ethical-humanistic as a challenge of medical practices that connote scientific and professional knowledge. In the article, it is proposed as a goal of reflecting on psychiatric practice from a bioethical vision, for the integral medical care of psychiatric patients who contribute to perfecting care in accordance with the social commission in the Psychiatric Hospital. The medical and directive experience was enriched with the application of theoretical, empirical and statistical methods. As a result, a new scientific logic is evidenced that takes into account autonomy as a bioethical principle in comprehensive medical care to psychiatric patients, considering vital bioethical-source treatment, in the solution of health problems.
Keywords: psychiatric practice; bioethics; Psychiatry; health relations